Diseño y Evaluación Ergonómica de Interfaces Físicas para la Órtesis Robótica de Tobillo (T-FLEX) a través de la Integración de Superficies Blandas - Rodríguez García, Nicolás (Ingeniería Biomédica, 2019)
Durante las últimas dos décadas se han desarrollado diversas órtesis y exoesqueletos con el fin de mejorar los patrones de marcha de las personas afectadas por enfermedades relacionadas al accidente cerebro vascular (ACV), un accidente cerebrovascular sucede cuando el flujo de sangre a una parte del cerebro se detiene. La órtesis activa T-Flex está enfocada en la rehabilitación de tobillo, y esta dirigida a personas que tengan una patología que limite la movilidad de esta articulación, como lo son el accidente cerebrovascular, parálisis cerebral o lesiones de medula. Para esto el T-Flex cuenta con dos modos de funcionamiento, ; (1) el modo de terapia donde el usuario esta sentado y el T-Flex realiza movimientos de dorsiflexión y plantarflexión a la velocidad y grado de movimiento que se requiera; (2) el modo de marcha, donde el usuario puede caminar con el T-Flex y este por medio de un sensor detecta la fase de marcha para realizar los movimientos de dorsiflexión y plantarflexión según el movimiento del usuario. En el contexto de este proyecto, se desea realizar una mejora de la ergonomía del sistema de la interfaz física de la órtesis. Es decir, se busca mejorar la parte de la órtesis en contacto con el usuario, por medio de diferentes materiales y superficies blandas. Esta mejora se plantea con el fin que la órtesis sea lo más cómoda para el uso durante una terapia de rehabilitación o incluso el uso en actividades de la vida diaria. La interfaz física anterior disipaba la fuerza en esfuerzo cortante, de compresión y generaba un desalineamiento sobre el cuerpo, lo que causaba que el dispositivo no pueda funcionar de manera correcta y pueda generar incomidad en el usuario. Con el fin de mejorar las interfaces físicas, primero se realizó una revisión de diferentes materiales que cumplieran ciertos criterios como ser ligero, suave, de bajo costo y de fácil manipulación. Estas características se buscaron con el fin de mejorar aspectos clave de la interfaz como el tamaño, el peso y la baja adherencia. El material escogido fue el poliuretano flexible, una espuma que se prepara a partir de una base y un catalizador. Al variar la proporción de estos componentes se pueden obtener densidades diferentes según los porcentajes que se usen en la mezcla para la obtención del material, es decir al aumentar o disminuir la proporción del catalizador se consiguen densidades diferentes del poliuretano. Una vez escogido el material, habiendo revisando los criterios de selección detallados en el documento, se procedió a realizar diferentes interfaces físicas con dicho material, cada interfaz consiste en un par de espumas que están ubicadas en la parte frontal (tibial anterior) y en la parte trasera (gastrocnemio) de la pierna, ya que estas son las partes donde el T-Flex está en contacto con el usuario. En cuanto al poliuretano flexible, se realizaron diferentes espesores desde 2cm hasta 4cm y con diferentes densidades 60 %-40% hasta 80 %-20 %. Se eligen estas proporciones debido a que son más fáciles de obtener ya que una densidad muy alta crearía una espuma de poliuretano demasiado rígida y una densidad muy baja haría una espuma de poliuretano altamente flexible haciendo que no mantenga su forma ni se pueda usar en la aplicación de este trabajo de grado. De esta manera se obtienen 9 interfaces físicas, por cada espesor 3 densidades diferentes, con el objetivo de probar cuales eran efectivas y cuál era la más ergonómica en cuanto a términos de comodidad. Por último, las interfaces se cubrieron con tela deportiva y a esta se le aplicó una silicona Dragon Skin TM, con el fin de mejorar la adherencia del T-Flex al usuario. Para evaluar las interfaces propuestas, primero se realizó una prueba con el modo de terapia durante 5 minutos, a velocidad media y con un rango de movimiento normal, donde cada una de las 9 interfaces se probó en 10 voluntarios sanos. El fin de esta prueba es observar si la interfaz se desplaza respecto a su posición inicial, si esta presenta un desplazamiento de más de 2cm se considera no efectiva. En esta prueba solo 7 interfaces se consideraron efectivas, por lo que con estas se procedió a realizar la prueba 2. Para la segunda prueba, los voluntarios debían caminar con el T-Flex durante 5 minutos en una banda sin fin, mientras se medía el EMG en los músculos en contacto con la interfaz, el gastrocnemio medial y el tibial anterior. A su vez también se midieron los parámetros espacio-temporales de la marcha, como lo son la cadencia, la velocidad de la marcha y la longitud de la zancada mediante el dispositivo G-Walk. Después de los 5 minutos se midió el desplazamiento final de la interfaz, comparando la posición inicial de la interfaz versus la posición final de la interfaz al momento de culminar la prueba. Por último cada voluntario debía responder un cuestionario basado en las Confort Rating Scales, con el fin de determinar cuál fue la interfaz más cómoda para la mayoría de voluntarios. Finalmente después de realizar las pruebas y analizar los resultados, se determinó que las mejores interfaces fueron las de mayor espesor, puesto que esta característica ayuda a que la interfaz realice una mayor presión sobre la pierna de los usuarios y de está manera garantizar que el dispositivo no se deslice o se mueva durante su uso. Como se puede apreciar en los resultados, dichas interfaces generan una menor carga de trabajo. En cuanto a los parámetros del G-Walk, el promedio de la cadencia y longitud de zancada fue más cercano a los rangos normales. Acerca de las medidas de desplazamiento, la interfaz de 4cm con densidad 80 %-20% es la que presento el menor desplazamiento siendo de 0.2cm únicamente en una prueba. Con el cuestionario se confirmo que las interfaces de espesor mayor son las que mejores valoraciones tuvieron. De acuerdo a todos los resultados obtenidos, se puede plantear hipotéticamente que la interfaz que tuvo un mejor desempeño durante las pruebas fue la interfaz de 4cm con densidad 80-20, puesto que esta tuvo el mejor desempeño en la primera prueba y se obtuvieron buenos resultados en la segunda prueba.

Over the past two decades, various orthoses and exoskeletons have been developed to improve the walking patterns of people affected by related diseases. to improve the gait patterns of people affected by diseases related to cerebrovascular accident (CVA), a stroke occurs when the flow of blood through the brain is impaired. stroke (stroke), a stroke occurs when blood flow to a part of the brain stops. flow of blood to a part of the brain stops. The T-Flex active orthosis is focused on ankle rehabilitation, and is targeted rehabilitation, and is aimed at people who have a pathology that limits the mobility of this joint, such as mobility of this joint, such as stroke, cerebral palsy or spinal cord injury. spinal cord injuries. For this, the T-Flex has two modes of operation, (1) the therapy mode where the user is seated and the T-Flex where the user is seated and the T-Flex performs dorsiflexion and plantarflexion movements at the speed and degree of motion at the speed and degree of movement required; (2) the walking mode, where the user can walk with the T-Flex T-Flex detects the walking phase by means of a sensor to perform dorsiflexion and plantarflexion movements at the speed and to perform dorsiflexion and plantarflexion movements according to the user's movement. In the context of this project, we want to improve the ergonomics of the physical interface of the orthosis. the physical interface of the orthosis. In other words, the aim is to improve the part of the orthosis that is in contact with the user, by means of different materials and soft surfaces. This improvement is aimed at making the orthosis to make the orthosis as comfortable as possible for use during rehabilitation therapy or even for use in activities of daily living. use in activities of daily living. The previous physical interface dissipated force in shear and compressive stress and generated and compression and generated a misalignment on the body, which caused the device to be unable to function properly. the device could not function properly and could generate discomfort for the user. In order to improve the physical interfaces, we first conducted a review of different materials that met certain criteria such as materials that met certain criteria such as being light, soft, low cost and easy to handle. These characteristics were sought in order to improve key aspects of the interface, such as size such as size, weight and low adhesion. The material chosen was flexible polyurethane, a foam that is prepared from a base and a catalyst. By varying the proportion of these components different densities can be obtained depending on the percentages used in the mixture to obtain the material. in the mixture to obtain the material, i.e. by increasing or decreasing the proportion of the catalyst, different densities of the polyurethane can be obtained. catalyst, different densities of the polyurethane are obtained. Once the material has been chosen, having reviewed the selection criteria detailed in the document, we proceeded to perform different physical interfaces with the material. different physical interfaces with this material, each interface consists of a pair of foams that are located on the front side of the each interface consists of a pair of foams that are located in the front part (anterior tibial) and in the back part (gastrocnemius) of the leg, since these are of the leg, since these are the parts where the T-Flex is in contact with the user. On As for the flexible polyurethane, different thicknesses were made from 2cm to 4cm and with different densities of different densities 60 %-40 % to 80 %-20 %. These proportions were chosen because they are easier to obtain since a very high density would create a polyurethane foam too rigid and a very low density would create a polyurethane foam too stiff. too rigid and a very low density would create a highly flexible polyurethane foam, causing it to and would not hold its shape and would not be usable in the application of this degree work. application. In this way 9 physical interfaces are obtained, for each thickness 3 different densities, in order to test which ones were effective and which one was the most ergonomic in terms of comfort. in terms of comfort. Finally, the interfaces were covered with a sports fabric and a Dragon Skin silicone was applied to it. Dragon Skin TM silicone was applied to the fabric in order to improve the adherence of the T-Flex to the user. In order to evaluate the proposed interfaces, a test was first performed with the therapy mode for 5 minutes, at medium speed and with a normal range of motion, where each of the 9 interfaces was tested on 10 healthy volunteers. The purpose of this test is to observe whether the The purpose of this test is to observe if the interface is displaced with respect to its initial position, if it presents a displacement of more than 2cm, it is considered ineffective. 2cm is considered ineffective. In this test only 7 interfaces were considered to be effective, so these were used to proceed with In this test, only 7 interfaces were considered effective, so test 2 was performed with these. T-Flex for 5 minutes on a treadmill, while the EMG was measured in the muscles in contact with the T-Flex. EMG was measured in the muscles in contact with the interface, the medial gastrocnemius and tibialis anterior. Spatiotemporal parameters of gait were also measured, such as cadence, gait speed, cadence, speed of gait, and gait velocity. cadence, gait speed and stride length were also measured using the G-Walk device. G-Walk device. After the 5 minutes, the final displacement of the interface was measured, comparing the initial position of the interface versus the final position of the interface at the end of the test. the test. Finally, each volunteer was asked to answer a questionnaire based on the Comfort Rating Scales, in order to determine which interface was the most comfortable for the majority of volunteers. volunteers. Finally, after conducting the tests and analyzing the results, it was determined that the best interfaces were those with the greatest thickness, the thickest, the most comfortable, and the most comfortable. the best interfaces were the thicker ones, since this feature helps the interface to put more pressure on the leg. the interface to put more pressure on the user's leg and thus ensure that the device does not slip or slip off the leg. that the device does not slip or move during use. As can be seen in the results results, these interfaces generate a lower workload. As for the G-Walk's parameters of the G-Walk, the average cadence and stride length were closer to normal ranges. normal. Regarding the displacement measurements, the 4cm interface with density 80%-20% is the one with the lowest displacement. density is the one that presented the smallest displacement being 0.2cm only in one test. With the confirmed that the interfaces of greater thickness are the ones that had the best evaluations. had. According to all the results obtained, it can be hypothetically stated that the interface that had the best performance was the one with the highest thickness. that the interface that had the best performance during the tests was the 4 cm interface with a density of 80-20, since it had the highest density 80-20, since it had the best performance in the first test and good results were obtained in the second test. good results were obtained in the second test.
Keywords: Prótesis; Ergonomía; Aparatos ortopédicos; Robótica- Tobillo; Protesis; Biomateriales; Ergonomía; Ergonomics; Prostheses; Biomaterials; Ortesis; Orthotics